NIR-I Dye-Based Probe: A New Window for Bimodal Tumor Theranostics - Zheng, Fan; Huang, Xueyan; Ding, Jipeng; Bi, Anyao; Wang, Shifen; Chen, Fei; Zeng, Wenbin (Frontiers in Chemistry, 2022)
Near-infrared (NIR, 650-1700 nm) bioimaging has emerged as a powerful strategy in tumor diagnosis. In particular, NIR-I fluorescence imaging (650-950 nm) has drawn more attention, benefiting from the high quantum yield and good biocompatibility. Since their biomedical applications are somehow limited by their relatively low penetration depth, NIR-I fluorescence imaging probes have been under extensive development for recent years. This review summarizes the particular application of the NIR-I fluorescent dye-contained bimodal probes, with emphasis on the related nanoprobes. These probes have enabled us to overcome the drawbacks of individual imaging modalities as well as achieve synergistic imaging. Meanwhile, the application of these NIR-I fluorescence-based bimodal probes for cancer theranostics is highlighted.